Medida simultánea de rotaciones y traslaciones de un objeto en el plano a partir de la información de fase de una rejilla radial (2021)
This paper presents a strategy that allows to determine the position and orientation of an object in a plane. The method consists of analyzing a system of radial fringes adhered to the object and by means of a digital image process to determine its phase. This process requires the coordinates of the center with sub-pixel accuracy and the radial axis of the fringes. Using the Fourier transform method and performing a transformation of coordinate systems from rectangular coordinate into radial, it can be calculated the phase of fringe system and the center of the radial fringes. Thus, the phase of the radial fringes is used as an encoder for measuring angular positions and spatial positions of the object in the plane. Experimental evaluations show that the technique developed has sub-pixel accuracy in evaluating displacements and rotations of an object in the plane. It is evaluated the error introduced in the calculation of angular position and displacement of the object. The study of the influence of system parameters of radial fringes let to establish that the size and number of fringes are determining factors for the present method in order to reduce the error.